Play Like a Man : My Life in Poster Children - Marshack, Rose, 1965- (Book collections on Project MUSE., 2023)
"As a member of Poster Children, Rose Marshack took part in entwined revolutions. Marshack and other women seized a much-elevated profile in music during the indie rock breakthrough while the advent of new digital technologies transformed the recording and marketing of music. Touring in a van, meeting your idols, juggling a programming job with music, keeping control and credibility, the perils of an independent record label (and the greater perils of a major)-Marshack chronicles the band's day-to-day life and punctuates her account with excerpts from her tour reports and hard-learned lessons on how to rock, program, and teach while female. She also details the ways Poster Children applied punk's DIY ethos to digital tech as a way to connect with fans via then-new media like pkids listservs, internet radio, and enhanced CDs. An inside look at a scene and a career, Play Like a Man is the evocative and humorous tale of one woman's life in the trenches and online"--